Analysis of China’s Carbon Peak Achievement in 2025 - Ziheng Niu; Jianliang Xiong; Xuesong Ding; Yao Wu (Energies, 2022)
To solve the problem of rising energy use and CO2 emissions, China issued the 14th Five-Year Plan in 2020, emphasizing the need to reduce its carbon intensity and achieve a carbon emission peak before 2030. In order to estimate the future path of carbon peak in China, a novel dataset was constructed to analyze 30 provinces in China, and found that the realization of carbon peaking in 2025 requires a reduction of 1.072 million tons of carbon emissions in 2025, at which point peak carbon emissions will be 11,008.4 million tons. Due to this energy gap caused by carbon emission reduction the total amount of clean electricity has reached 3600 billion kWh. In carbon emission allowance trading, provinces with large carbon emissions, like Jiangsu and Guangdong, prefer to buy carbon allowances, while those with small carbon emissions like Shanxi and Inner Mongolia prefer to sell carbon allowances. In the energy trading market, the overall situation meets the 14th Five-Year Plan of west-east and north-south power transmission, except for Shanghai, Hainan, Hubei, and other provinces selling power, due to excessive power generation from a particular energy source.